2019
DOI: 10.1177/1176934319850821
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Microbiota Associated With Sperm of Malaysian Mahseer Tor tambroides

Abstract: Malaysian Mahseer ( Tor tambroides ) is considered as a good prospect for aquaculture in Malaysia. However, knowledge about Malaysian Mahseer-associated sperm microbiota is still limited, although some studies reported that sperm-related bacteria are a factor in the decline of sperm quality, as sperm may become the carrier of pathogenic bacteria to the egg. The goal of this study was to evaluate the sperm microbiota associated with Malaysian Mahseer from 3 different locations (Universiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
0
0
Order By: Relevance
“…These discrepancies could be explained in part by the differences in microbial community composition across body sites (Minich et al, 2020;Clavere-Graciette et al, 2022). In the seminal fluid, the diverse microbiota was predominantly composed of 4 main phyla, which include Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria (Koh et al, 2019), also found in a study based on denaturing gradient gel electrophoresis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These discrepancies could be explained in part by the differences in microbial community composition across body sites (Minich et al, 2020;Clavere-Graciette et al, 2022). In the seminal fluid, the diverse microbiota was predominantly composed of 4 main phyla, which include Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria (Koh et al, 2019), also found in a study based on denaturing gradient gel electrophoresis.…”
Section: Discussionmentioning
confidence: 95%
“…Major taxonomic composition shifts were observed (ANCOM approaches) between wild and aquarium small-spotted catsharks in Serratia, Salinisphaera and Cutibacterium genera, being higher in managed care sharks, a factor associated with dysbiosis in other species (Garcia-Segura et al, 2022). Salinisphaera was ubiquitous in the Malaysian Mahseer sperm microbiota (Koh et al, 2019). Correspondingly, Cutibacterium has been identified in rays and skates (Goncalves et al, 2020;Mika et al, 2021;Garcia-Segura et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Bacteroides sp. supplementation improves the sperm quality of Tor tambroides [191]. Application of Lab.…”
Section: Malementioning
confidence: 99%